Distinguishing rosacea from sensitive skin by reflectance confocal microscopy - Ma, Yafeng; Li, Lulu; Chen, Jia; Chen, Tian; Yuan, Chao (Skin research and technology, 2020)
Background The updated standard classification and pathophysiology of rosacea have provided clear and meaningful evaluation parameters; however, differentiating rosacea from sensitive skin (SS) remained an obstacle for dermatologists around the world, especially in China. Herein, we aimed to find a better characteristic to distinguish rosacea from SS by using reflectance confocal microscopy (RCM). Method Forty rosacea patients and 143 healthy subjects were recruited in this study. Firstly, a SS questionnaire and a lactic acid sting test were conducted among healthy subjects. Next, two major groups were divided out, including a SS group (40 subjects) and a normal skin control group (NS, 60 subjects). The cutaneous structures of face and fossa cubitalia were imaged by RCM. Results We found that more parakeratosis, honeycomb pattern, spongiform edema, and dermal papillae (P < .05) in rosacea patients than that of the NS group, whereas there were no significant differences, were found in rosacea patients and the SS group. Strikingly, we found that rosacea patients have a larger depth of honeycomb pattern than that of SS subjects (P < .05). But, the epidermal thickness of rosacea did not differ from that of SS groups. There was also no significant difference of epidermal thickness and honeycomb structure depth between rosacea patients and NS group. Conclusion From the RCM images of parakeratosis, honeycomb pattern, spongiform edema, and dermal papillae, we found that RCM might be a faithful tool to distinguish rosacea from NS group. The depth of honeycomb structure of SS was more superficial than rosacea patients, whereas no significant difference between rosacea patients and NS group. RCM may provide a new method for evaluating the development of rosacea although it failed to distinguish rosacea and SS effectively.